Impact of gridded weather data sources and its temporal resolution on crop evapotranspiration and effective rainfall of major crops in eastern region of India - Paramaguru, Pradosh Kumar; Mali, Santosh Sambhaji; Shirsath, Paresh B. (Indian Society of Agricultural Engineers, 2022)
Synthetic climate data are being increasingly used as key input in number of climate change impact assessment studies, hydrological assessments, and water resource management projects. The present study quantified the impact of two-gridded climate data sources [India Meteorological Department (IMD) and National Oceanic and Atmospheric Administration (NOAA) Climate Prediction Centre (CPC)] on estimation of evapotranspiration (ET) and effective rainfall (ER) of paddy (Kharifj and wheat (Rabi) crops across four agro-ecological sub-regions, and compared the results with observed station data. The effect of daily, decadal, and monthly temporal resolutions of climatic data were evaluated on ET and ER using climatological model CROPWAT 8.0. Results showed that compared to daily resolution, the monthly temporal resolution estimated significantly higher (1.7–4.0%) ET for wheat crop. Effect of temporal resolution of climate data on ER of both crops was insignificant, implying that the uncertainties in estimation of ER emanating from use of daily, decadal, or monthly temporal resolutions would be within acceptable limits. Across the locations, the CPC-based estimates of paddy ETc deviated from (−)1.3% to 21.6% of the station ET, while the deviations for wheat ET were in the range of (−)7.1% to 9.3 per cent. Significant variations from station etc were also observed for CPC (1.7 - 19.4%) and IMD [(−)34.3 - 31.1%] based ET estimates of wheat ET. The study recommends that the technological and policy research outputs based on gridded climate data products should be carefully analysed keeping in view the uncertainty accruing on account of use of gridded data products.